Impact Of The Instability Of Trade Flows On Economic Growth In Benin - DOSSOU, Blanchard Felix (Archives of Business Research, 2020)
This article has discussed the impact of volatile trade flows on economic growth in Benin. The analysis is conducted by a VAR model inspired by the neoclassical production function. The study data are time series covering the period from 1980 to 2016. At the end of the study, it can be deduced that a shock on the degree of openness is negatively and significantly reflected on economic growth over two years. The variance of errors in the GDP growth rate explained by the degree of openness is 3.17%. The correlation coefficient between growth rate and openness errors is -0.56. There is a positive and significant contribution of the capital factor to growth from the 4th year. As for the labor factor, its positive effects on growth are statistically zero. In order to mitigate the effect of trade opening shocks on the level of growth, Benin should process its agricultural products locally, on the one hand, and diversify its export products, on the other.